TEACHING READING COMPREHENSION THROUGH CONCEPT ORIENTED READING INSTRUCTION (CORI) STRATEGYTO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 13 LUBUKLINGGAU - ardayati ardayati; herlina herlin (STKIP PGRI Lubuklinggau, 2019)
The problem of this research was to find out whether or not it is significantly effective to improve reading comprehension through Concept Oriented Reading Instruction (CORI) Strategy to the Eighth Grade Students of SMP Negeri 13 Lubuklinggau in the academic year 2016/2017. The strategy applied was pre experimental method with one group pretest-posttest design.. The sample was taken through cluster random sampling. The result was VIII.2 class with the total number of 28 students. The data were collected through test consisted of 25 items of multiple choices. The data were analyzed through four techniques: 1) Students’ Individual Score, 2) Minimum Mastery Criteria, 3) Normality and 4) Paired t-test calculation. The result of this study: (1) The mean students’ score in the pre-test was 64.00, (2) The mean score of post-test was 76.00 and (3) the result of paired t-test was 11.43, which was higher than 1.703 value of the t-table of 27 (28-1) with 95% significant level for one tailed-test. In this research the researcher formulated two hypotheses. They were null hypothesis (Ho) and alternative hypothesis (Ha). Based on the result of the paired t-test calculation showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It meant that it was significantly effective to Teach Reading Comprehension through Concept Oriented Reading Instruction (CORI) Strategy to the Eighth Grade Students of SMP Negeri 13 Lubuklinggau in the academic year of 2016/2017